2012
DOI: 10.1159/000338502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on PTHrP and PTHrP Receptor Expression in Rat Coronary Endothelial Cells

Abstract: Aims: The study was aimed to investigate whether nicotine affects endothelial expression of PTHrP and PTHrP receptor, a peptide system involved in endothelial protection against apoptosis. Methods: Isolated and cultured rat coronary endothelial cells were used. Immunoblot techniques were used to study activation of mitogen-activated protein (MAP) kinases and to quantify PTHrP and PTHrP receptor expression. Real-time RT-PCR was used to quantify PTHrP, PTHrP-receptor, bcl-2, and bax mRNA expression. The rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Furthermore, we have recently shown that nicotine reduces PTHR1 expression in microvascular endothelial cells by activating acetylcholine receptors (Röthig et al. ). Considering that high physical activity is associated with an activation of the parasympathetic nervous system as indicated by lower resting heart rate (Schreckenberg et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we have recently shown that nicotine reduces PTHR1 expression in microvascular endothelial cells by activating acetylcholine receptors (Röthig et al. ). Considering that high physical activity is associated with an activation of the parasympathetic nervous system as indicated by lower resting heart rate (Schreckenberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Blots were incubated with a monoclonal antibody directed against PTHR1 (antibody SAB4502493, Sigma‐Aldrich, St. Louis, USA) as described before (Röthig et al. ) and a second antibody coupled to horseradish peroxidase (anti‐Actin [antibody A2668, Sigma‐Aldrich, St. Louis, USA]) and anti‐GAPDH (antibody 6C5 from Calbiochem EMD Chemicals, San Diego, USA). Specificity of the PTH‐1R antibody was proven by strong exposure of the samples and the absence of upcoming unspecific bands under these conditions and downregulation of the receptor in microvascular endothelial cells (see Röthig et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein samples were loaded on NuPAGE Bis-Tris Precast gels (10%; Life Technology, Darmstadt, Germany) and subsequently transferred onto nitrocellulose membranes. Primary antibodies directed against PTHrP, PTH-1 receptor and α-actin (loading control) were used as described before [20].…”
Section: Methodsmentioning
confidence: 99%
“…Samples (100 μg) were loaded on a 12.5% SDS‐PAGE and blotted onto membranes as described before 22. Blots were incubated with a monoclonal antibody directed against PTHrP (antibody GF08; Calbiochem, Bad Soden, Germany) or PTH‐1 receptor (antibody 3D1.1; Upstate biotechnology, Eschborn, Gerrmany) as described before 28 and a second antibody coupled to horse radish peroxidase. Surfactant production was quantified by immunoblots detecting surfactant protein‐C (SP‐C; antibody FL‐197, sc‐13979 Santa Cruz Biotechnology) and lipofibroblast‐to‐myofibroblast transdifferentiation was analysed by up‐regulation of α‐smooth muscle protein (antibody clone 1A4, C6198 from Sigma‐Aldrich; St. Louis, USA).…”
Section: Methodsmentioning
confidence: 99%